Multimedia-Based Discovery Learning Approach to Improve Critical Thinking Skills and Student Learning Outcomes - Yuniarti, Nenik; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2020)
The purpose of this study was conducted to determine the increase in critical thinking skills and student learning outcomes in multimedia-based elasticity learning and discovery learning. The type of research used is action class research with 3 cycles. Each cycle consists of 4 stages, namely planning (action), action (action), observation (observation) and reflection. The sample used was class XI IPA 2 SMA Negeri 2 Pekalongan. The critical thinking skills of students in cycle 1 are still in the low category, but the positive behavior of students has begun to appear. The participation of students in discussions increases. Critical thinking skills in cycle 2 increased with good categories. Students who are usually lazy have started to join the discussion. The increase in critical thinking skills occurred in the third cycle with the very good category, because in this cycle the discussion groups were divided based on the peer tutor principle. The percentage of student learning outcomes also increased to 74%. This increase can be seen in the acquisition of a gain value of 0.55 in the medium category. Multimedia-based learning with discovery learning models can be applied in learning physics so that it can improve student learning skills and outcomes